Two-Dimensional River Flow Patterns Observed with a Pair of UHF Radar System - Yidong Hou; Biyang Wen; Yonghuai Yang; Jing Yang; Caijun Wang (International Journal of Antennas and Propagation)
A pair of ultrahigh-frequency (UHF) radars system for measuring the two-dimensional river flow patterns is presented. The system consists of two all-digital UHF radars with exactly the same hardware structure, operating separately at 329–339 MHz and 341–351 MHz. The adoption of direct radio frequency (RF) sampling technique and digital pulse compression simplifies the structure of radar system and eliminates the distortion introduced by the analog mixer, which improves the SNR and dynamic range of the radar. The field experiment was conducted at Hanjiang River, Hubei province, China. Over a period of several weeks, the radar-derived surface velocity has been very highly correlated with the measurements of EKZ-I, with a correlation coefficient of 0.958 and a mean square error of 0.084 m/s.